Análise e calibração de modelo constitutivo para fluidos dependentes do tempo - Kroetz, Fernando Machado (2020)
In the present work a mathematical model is developed and numerical simulations are conducted regarding rheometrical experiments for time-dependent fluids. The mathematical model considers the material thixotropy from the microstructural indirect approach, without using structural parameters. The properties evolution is ruled by the unbalance between their instantaneous values and the equilibrium ones. Two main materials were employed for the rheometrical experiments: laponite suspension and drilling fluid. Rheometrical experiments were developed at CERNN/UTFPR using the rheometers Anton Paar MCR 702 TD and TA DHR 3. The experiments consisted on obtaining the flow curve, start-up from controlled shear rate and creep tests, as well as restructuring experiments from oscillatory tests. These experiments were employed in order to fit the parameters from the mathematical model. The laponite sample showed a complex behavior, where shear bands were found and the steady state was not achieved for both the oscillatory and creep experiments. These behaviors were not found for the drilling fluid. For the start-up from a shear rate step the mathematical model presents initially the elastic growth of the shear stress, followed by the shear stress overshoot and further material relaxation until the steady state is achieved. For the restructuring oscillatory experiment, the storage and loss moduli increase until reaching the steady state, and for the creep experiments the mathematical model is able to predict the avalanche effect. The numerical simulations for both materials show that the model is able to represent the main characteristics of elasto-viscoplastic thixotropic materials and can be a useful alternative to classic microstructural models that employ microstructural parameters.